Characterization of polysaccharide extracts recovered from different grape and winemaking products. (July 2022) - Canalejo, Diego; Guadalupe, Zenaida; Martínez-Lapuente, Leticia; Ayestarán, Belén; Pérez-Magariño, Silvia; Doco, Thierry
Graphical abstract: Highlights: Grape polysaccharides were extracted from different sources: pomace, must, wine, lees. Grape polysaccharide composition depends on the matrix used for the extraction. Grape by-products can emerge as a potential source of polysaccharides. White pomace is a good source to obtain valuable grape by-products rich in polysaccharides. Abstract: One of the most important challenges of the oenological industry is the recovery and valorization of valuable compounds from grapes and grape by-products. Recent studies have focused on the obtention of phenolic compounds, but little attention has been paid to the extraction of grape polysaccharides, which could have a great potential as oenological products but also for their benefits to human health. This study aimed to recover polysaccharides from different grape and winemaking products and provide information about its composition. The results obtained with the white pomace and white lees revealed its potential to be exploited to obtain extracts rich in polysaccharides. White pomace revealed as a good source to obtain polysaccharides rich in arabinose and galactose (PRAG) and glucosyl polysaccharides. White lees showed a potential to be used to recover mannoproteins and glucans. Both extracts showed high polysaccharide purity (55.5% and 51.9%, respectively). Extracts rich in rhamnogalacturonan type II (RG-II) were obtained from a red wine (89.7% polysaccharide purity) and from the wash water used by the distillery after draining the distilled wine pomace (40.6% polysaccharide purity). Our results open new lines to obtain extracts with different polysaccharide composition, non-available in the market. Future studies are needed to evaluate their potential as stabilizing or finning agents and possible alternative solutions to traditional animal-origin protein fining agents.